Pengaruh Terapi Non Farmakologi Dengan Media Murrotal Al-Qur’an Kombinasi Senam Dysmenorrhea Terhadap Penurunan Nyeri Haid Di Panti Asuhan Sejahtera Aisyiyah - Hamdiyah Hamdiyah (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Reproductive health is an important part of general health and main characteristic to increase the degree of human health from childhood, and most important is adolescence and adulthood. And determine the level of reproductive health for women dan men. This can affect future generations’ health. Women who have entered puberty will who experienced menstruation, most of women will experience discomfort or painful periods and usually called by dysmenorrhea. Dysmenorrhea Management can used by pharmacological and non-pharmacological therapy that have been carried out as an effort to overcome dysmenorrhea such as analgesic drugs, hormonal therapy, non-steroidal prostaglandin drugs, and dilatation of the cervical canal. This therapy can Addiction and Negative Effects and drug side effects is dangerous for patient while non-pharmacological therapy common is relaxation therapy with listening to music, acupuncture, acupressure, sports, and spiritual therapy. One of non-pharmacological therapy is gymnastics / sports, and spiritual therapy that is usually by dzikir also listening the holy Quran recitation able to provide a relaxing effect because it can activate the relaxing effect because it can activate the hormone endorphin.The research is quasi eksperimental model with the pretest- posttest two group design. The sample of this research that adolence in Panti Asuhan Sejahtera Aisyiyah Pangkajene, Sidrap. Respondent recruitment by using purposive sampling. The data analysis used independent t-test.The research result from independent t-test, The results showed there is a significant effect of non farmakologi therapy with murottal therapy (Al-Qur'an) combination dysmenorrhea gymnastics in reducing pain level.. Results of the analysis (Pv = 0.000) <α (0.005) each month is the first month, the second month and the thirdh month.